Distance-based target tracking algorithm in binary sensor network - SUN Xiao-yan1; LI Jian-dong1; HUANG Peng-yu1; ZHANG Wen-zhu1 (Tongxin xuebao)
A distance-based target tracking algorithm for binary sensor network was proposed.This algorithm can decide the output bit information and compute the weighting simultaneously.The simulation is used to validate the effectiveness of distance-based weighting scheme.This algorithm has good performance,when the target moves linearly,curvilinear,or randomly through the sensing field,and the error distribution of single target position is in .